2018
DOI: 10.3390/v10040188
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Phage Genomes for Therapeutic Applications

Abstract: Multi-drug resistance is increasing at alarming rates. The efficacy of phage therapy, treating bacterial infections with bacteriophages alone or in combination with traditional antibiotics, has been demonstrated in emergency cases in the United States and in other countries, however remains to be approved for wide-spread use in the US. One limiting factor is a lack of guidelines for assessing the genomic safety of phage candidates. We present the phage characterization workflow used by our team to generate dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
103
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(107 citation statements)
references
References 60 publications
0
103
0
Order By: Relevance
“…These phages were characterized by electron microscopy, one-step growth experiments, and genome sequencing. Sequence analysis confirmed that P1 and P2 were related to strictly lytic phages and that neither phage harbored an identifiable integrase, toxin, or bacterial virulence factor, satisfying several recommended criteria for therapeutic phage selection (14).…”
Section: Resultsmentioning
confidence: 80%
“…These phages were characterized by electron microscopy, one-step growth experiments, and genome sequencing. Sequence analysis confirmed that P1 and P2 were related to strictly lytic phages and that neither phage harbored an identifiable integrase, toxin, or bacterial virulence factor, satisfying several recommended criteria for therapeutic phage selection (14).…”
Section: Resultsmentioning
confidence: 80%
“…Therefore, guidelines are needed to analyze and differentiate phages designated for therapy in humans or animals by their lifecycle. Such guidelines do not yet exist [85]. The US FDA, for example, relies on emergency protocols proposed by medical doctors for the case-by-case approval of phage cocktails for therapeutic purposes in special "compassionate" use of Investigational New Drugs (IDEs).…”
Section: Determining Safety Of Phages In the Era Of "Omics"mentioning
confidence: 99%
“…After identifying the endolysin gene E-LM12 (gp159) from the S. aureus vB_SauM-LM12 phage genome 46 , a BLAST analysis revealed that E-LM12 shows high similarity with endolysins from several staphylococcal phages, including Staphylococcus phage MCE-2014 (100% coverage, 95% identity) 47 , Staphylococcus phage phiIPLA-RODI (100% coverage, 94% identity) 48 and Staphylococcus phage vB_SauM_0414_108 (99% coverage, 95% identity) 49 . Also, no similarity was found with endolysins from phages infecting other bacterial genera.…”
Section: Bioinformatics Analysis Of E-lm12mentioning
confidence: 99%